In-vivo administration of histone deacetylase inhibitors does not impair natural killer cell function in HIV+ individuals. (15th March 2019) - Garrido, Carolina; Tolstrup, Martin; Søgaard, Ole S.; Rasmussen, Thomas A.; Allard, Brigitte; Soriano-Sarabia, Natalia; Archin, Nancie M.; Margolis, David M.
Abstract : Objective: Histone deacetylase inhibitors (HDACi) have proven to induce HIV-RNA and antigen expression in resting CD4 + T cells of antiretroviral therapy (ART)-treated HIV-infected individuals. However, to achieve viral eradication, immune clearance must follow latency reversal, and thus it is essential to understand the impact of latency reversal agents on immune function. Design: Here we evaluate the impact of in-vivo administration of vorinostat (VOR) and panobinostat (PNB) during clinical trials on natural killer (NK) cell function and phenotype. Methods: Cryopreserved peripheral blood mononuclear cells from HIV-positive participants receiving VOR (NCT01319383) or PNB (NCT01680094) were selected to assess the impact of the drugs on cell composition, activation, NK cell phenotype (CD16, NKG2D, NKp30, NKp46 and DNAM-1), cytotoxic activity (CD107a), and interferon (IFN)-γ production. Results: No impairment of NK cell function was observed during treatment with either VOR or PNB. An increase in the frequency of CD3 − CD56 + NK cells was consistently observed. Interestingly, after VOR administration, NK cells increased expression of NKp46 and CD16, and showed improved degranulation and IFN-γ production capacity. Moreover, taking together VOR and PNB samples, HIV DNA levels in CD4 + cells were negatively correlated with NK cell frequency and NK cell expression of CD16. Conclusions: In-vivo treatment with HDACi does not have measurable negative effects on NK cell function, with some evidence of improved function in vitro . These results have important implications for potential combinatorial approaches to target HIV reservoirs, suggesting that the use of HDACis as a latency reversal agent could be paired with interventions to enhance NK cell activity or recruitment.